Questioning the myths of origin : Amir Muhammad's historical film about the Communist Party of Malaya and Malaysian independence / Wan Aida Wan Yahaya - Wan Yahaya, Wan Aida (UPENA, 2008)
Malaysian independent filmmaker Amir Muhammad has become known internationally for his witty and satirical documentaries on Malaysia and Malaysian society. One of Amir's latest works, Lelaki Komunis Terakhir ('The Last Communist', 2006), was well received internationally. However, the film has been banned in Malaysia. This documentary recounts the life of exiled Communist Party of Malaya leader, Chin Peng, now living in exile in Southern Thailand. The film was inspired by Chin Peng's autobiography, 'Alias Chin Peng: my side of history' (2003). In his film Amir juxtaposes Chin Peng's life (past and present) against scenes of modern day Malaysia, simultaneously exploring issues of social development and progress, and notions of loyalty to the state and to a cause. The paper has a number of aims. Firstly it examines the circumstances of the banning of the film and the reasons or justifications given for the ban. Secondly it highlights and explores a main contention put forward by the filmmaker, the need to reexamine the role of the much maligned Communist Party of Malaya in the Malaysian independence movement in the period leading to independence from the British, and particularly the function and contribution of Chin Peng in this period, an aspect of Malaysian history that has been suppressed since independence in 1957. Thirdly it examines Amir Muhammad's alternative documentary style, and his mode of raising issues about contemporary Malaysia by via processes of ironic commentary and subtle juxtaposition.